THE EFFECTIVENESS OF LAW ENFORCEMENT IN STRENGTHENING STATE INTELLIGENCE TO COUNTERACT INFORMATION SYSTEM HACKING AS A THREAT TO THE SOVEREIGNTY OF THE INDONESIAN NATION - Syukur Kasieli Hulu (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The rapid development of information technology has opened up opportunities for the emergence of new threats to national security, one of which is the hacking of information systems. Cyber attacks not only cause economic losses and disruption of public services, but also pose a serious threat to Indonesia's digital sovereignty. In this context, state intelligence has a strategic role as the frontline in detecting, analyzing, and counteracting various forms of threats to the country's strategic information systems. However, strengthening the state intelligence function in the face of hacking crimes still faces various obstacles, both from the aspects of regulations that have not been adaptive, weak inter-agency coordination, to limited technology and human resources. This study aims to examine the effectiveness of strengthening state intelligence in counteracting hacking of information systems, and formulate the urgency of national legal policy reforms that support the formation of a strong, integrated, and professional cyber intelligence system. Using normative legal research methods supported by conceptual and case approaches, this study concludes that strengthening state intelligence requires regulatory reform, institutional integration, and investment in technology and human resources to maintain the nation's sovereignty in the digital era.Keywords: State Intelligence, Hacking, Digital Sovereignty, Cyber Security, Legal Policy.